2RUS/RRS Parallel Mechanism and Its Kinematics Analysis - Geng Mingchao; Zhao Tieshi; Zhang Canguo (Jixie chuandong)
Based on the motion characters of the running cars,a foldable 2 RUS/2 RRS parallel mechanism is proposed as a car motion simulation platform. The geometrical relationship of force screw supplied by the branches is obtained,and the degrees of freedom feature is gotten. Also,based on the Grassmenn geometry,the input selection rationality of the mechanism is analyzed. The screw can simplify the representation of rigid body motion,and has geometric intuitiveness and algebraic abstractness. Referring to the screw algebra and the influence coefficient theory,the screw velocity and acceleration mapping relation of the mechanism are given by adding virtual joint. Using polyline in the ADAMS software,the mechanism model is established,and the numerical validation is performed on the theory of kinematics modeling of the mechanism.